Oralidade e Escrita: tradição e renovação no contar de Ricardo Azevedo - Silva, Ana Paula Bezerra Correia da (2016)
This dissertation aims to analyze the retelling of the book No meio da noite escura tem um pé de maravilha ( In the middle of the dark night there is a wonder tree – in a literal translation) by Ricardo Azevedo. It is discussed here how the rewriting of these popular narratives preserves the essence of the oral traditional literature and its mythical structure, giving them a new meaning in nowadays reality. In order to support this study, a investigation about preservation and updating of oral tradition on the chosen corpus was done, as well as a comparison to other versions, such as learning the way how the author perpetuates the mythical framework and, eventually this dissertation goals to reflect about the refunctionality of authory. The investigation raises a reflection on the concept of orality that trespasses the social area if the means of publication be considered. In our permanent worry, we tried to answer the following questions: how rewriting No meio da noite escura tem um pé de maravilha (In the middle of the dark night there is a Wonder tree) by Ricardo Azevedo retrieves an oral traditional literature? Does the updating of its narrative personify the myth? This work is founded on Paul Zumthor’s and Walter Ong’s critical-theoretical propositions concerning the concept of orality and also on Roland Barthes’ and Michel’s Focault’s concerning the authory issue. Also explored were the concepts defended by Vladimir Propp and Christopher Vogler about the archetype of hero. It is stated that the preservation of this literature depends on its constant modification in accord with time aspects and inevitable adaptation to circumstances as well as to its teller’s voices either in oral or written forms